A novel germline hyperactivating JAK2 mutation L604F - Dvořáček, Lukáš; Marková, Jana; Holoubek, Aleš; Grebeňová, Dana; Kundrát, David; Kuželová, Kateřina; Schwarz, Jiří (Annals of hematology, 2023)
Somatic JAK2 mutations are the main molecular cause of the vast majority of polycythemia vera (PV) cases. According to a recent structural model, the prevalent acquired V617F mutation improves the stability of the JAK2 dimer, thereby enhancing the constitutive JAK2 kinase activity. Germline JAK2 mutations usually do not largely alter JAK2 signaling, although they may modulate the impact of V617F. We found an unusual germline JAK2 mutation L604F in homozygous form in a young PV patient, along with a low allele burden JAK2 V617F mutation, and in her apparently healthy sister. Their father with a PV-like disease had L604F in a heterozygous state, without V617F. The functional consequences of JAK2 L604Fmutation were compared with those induced by V617F in two different in vitro model systems: (i) HEK293T cells were transfected with plasmids for exogenous JAK2-GFP expression, and (ii) endogenous JAK2 modifications were introduced into HeLa cells using CRISPR/Cas9. Both mutations significantly increased JAK2 constitutive activity in transfected HEK293T cells. In the second model, JAK2 modification resulted in reduced total JAK2 protein levels. An important difference was also detected: as described previously, the effect of V617F on JAK2 kinase activity was abrogated in the absence of the aromatic residue F595. In contrast, JAK2 hyperactivation by L604F was only partially inhibited by the F595 change to alanine. We propose that the L604F mutation increases the probability of spontaneous JAK2 dimer formation, which is physiologically mediated by F595. In addition, L604F may contribute to dimer stabilization similarly to V617F.
Keywords: HeLa buňky; zárodečné mutace; Janus kinasa 2; zárodečné buňky; Germ-Line Mutation; mutace; HEK293 Cells; lidé; Female; Mutation; ženské pohlaví; Germ Cells; HeLa Cells; Janus Kinase 2; HEK293 buňky; Humans